LAYOUT OF COMPUTER CLASSROOM - COMPARISON AND ANALYSIS OF POSSIBLE SOLUTIONS - DOSTAL, Jiri; KOPECKOVA, Zuzana (Trends in education, 2012)
This paper compares possible solutions of layout of computer classrooms. It analyzes the conditions to the needs of the educational process. Particular attention is given to the student and teacher as objects of research.
Keywords: ergonomics; computer lab; research; teacher; student.